Development of microencapsulate containing Hamamelis virginiana L. extract as a potential agent in derm cosmetic formulations (Research, Society and Development, 2023)
Due to the numerous benefits related to the Hamamelis virginiana L. extract, including its astringent and anti-inflammatory function, the plant has been extensively studied with the purpose of being increasingly used in cosmetics. Encapsulation, which is equally relevant when it comes to dermatological products, forms the perfect combination for a good beauty product with the extract. This process consists of coating a certain bioactive compound in a thin layer of polymeric material, sodium alginate, a biodegradable natural polysaccharide. In view of this, the objective was to produce microencapsulated H. virginiana using sodium alginate (encapsulant), evaluating its release profile. The microencapsules were prepared by dripping and crosslinking, subsequently subjected to the detection of phenolic compounds in a solution similar to skin acidity (pH 5.5), every 20 min for 120 minutes. In addition to the encapsulation process, the microencapsules were evaluated in terms of size and degree of imbibition. It was possible to obtain microencapsules (± 5mm) doped with H. virginiana extract in a ratio (1:4), satisfactorily allowing the immobilization of phenolic compounds, without pores, which would compromise their stability. The maximum release profile of the compounds (71.75 mg. L-1) occurred after 40 min, reaching imbibition stability after 60 min. The microencapsules produced have potential programmed release capacity for the incorporation of cosmetic formulations with tonic and antioxidant applications, resulting in an improvement in the appearance of the skin and thus inhibiting the aging process. The proposition makes room for the imprisonment of different bioactives capable of binding to other elements of biological interest.